Modeling of the acclimation/deacclimation process of a mixed culture degrading 4-chlorophenol - Buitrón, G (Water science and technology : a journal of the International Association on Water Pollution Research, 2004)
The variation of concentration of the toxic substrate has a negative effect on the sludge activity. Although this loss of activity of the microorganisms under toxic starvation has been reported, this variable is not taken into account in the operation of biological wastewater treatment plants. In order to monitor and control the biological plant with a certain confidence it is necessary to consider the acclimation and deacclimation processes to avoid the reactor malfunctioning, resulting in loss of efficiency or in false data acquisition during monitoring. This paper proposes a model for the acclimation/deacclimation process. The experiments have been done in a sequencing batch reactor during the 4-chlorophenol degradation. The basic idea of the model is to consider the variation of the kinetic parameters of the Haldane law in terms of the acclimation and deacclimation state. The idea is discussed, and the results obtained are presented